On the Initial Value Problem of Stochastic Evolution Equations in Hilbert Spaces. (12th April 2016) - Zhang, Xuping; Li, Yongxiang; Chen, Pengyu
Abstract : The present paper studies the initial value problem of stochastic evolution equations with compact semigroup in real separable Hilbert spaces. The existence of saturated mild solution and global mild solution is obtained under the situation that the nonlinear term satisfies some appropriate growth conditions. The results obtained in this paper improve and extend some related conclusions on this topic. An example is also given to illustrate that our results are valuable.